Study of blood count in the validity experimental appendicitis in rabbits - Ramos,Eduardo Chibeni Fernandes (1999)
A group of thirty six rabbits was studied, with weight ranging from 2400 to 3100 grams, in order to evaluate the blood test on the validity of experimental acute appendicitis. In order to do that, the animals were distributed amony three groups of 12 rabbits each, that corresponded to observation periods of 24 hours(Group A), 48 hours(Group B) and 72 hours(Group C). The presence of macroscopic appendicitis was verified in all the rabbits of the experiment on the three studied periods. The blood test study showed statistic significance when reading the values of haemoglobin, haematocrit and monocytes in Group C; of total and segmented leucocytes, eosinophiles, limphocytes and monocytes in Group B; when the groups faced each other, however, there was no estatistic significance. So, it was concluded that the values of haemoglobin, red blood, white cells and haematocrit are not suitable markers for experimental appendicitis in rabbits.